Seroprevalencia del virus de la hepatitis C en un banco de sangre de Medellín-Colombia, 2005-2018 (2023)
The objective of this study was to estimate the seroprevalence of hepatitis C virus (HCV) in donors of a Medellín-Colombia blood bank in the 2005-2018 period and to identify its associated factors. A mixed ecological study was conducted with 166603 donors. The description was made with frequencies, time series with seroprevalences and their 95 % confidence intervals. Odds ratios were estimated raw and adjusted by binary logistic regression in SPSS 25.0®. The seroprevalence was 0.567 % (95 % CI = 0.53-0.60) with a low and stable endemicity since 2010. The only factors that presented statistical differences in seroprevalence were the age group and the frequency of donation, with an infection 23 % higher in donors aged over 40 years (compared to people aged 18-40), and 94 % higher in first-time donors, compared to repeat ones. It is concluded that in Medellín the endemic levels of HCV have been stable and low in the last decade, evidencing the importance of the epidemiological surveillance carried out by blood banks. The lower prevalence in the last decade suggests a differential exposure to the virus depending on the generation to which it belongs, so that the birth cohort effect that should be studied in later research. © 2019, Universidad Nacional de Colombia. All rights reserved.